(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Aim: The aim of this study was to compare the attachment of the modified diamond post and the Erlangen post within the root canal. Materials and Methods: The research sample consisted of 30 healthy, single-canal human lower premolars extracted for orthodontic purposes, cleaned with periodontal curettes, and preserved in Timol solution during the research period. The dental crowns were cut, and the length of the canals was determined by inserting a #15 K file into the canal until it became visible, so the working length was equal to the length of the file minus 1 mm. The teeth were then prepared in the traditional method, then filled using the lateral condensation technique using zinc oxide and eugenol with gutta percha. The teeth were then placed in the incubator for 7 days at a temperature of 27 degrees Celsius and 100% humidity.The teeth were then divided into two equal groups (each group had 15 teeth), so that the Erlangen wedge was applied in the first group, and the modified diamond post in the second group. The sample was then subjected to a tensile test, the data was recorded, and appropriate statistical tests were conducted.Results: The diamond post bond streangth were greater than the Erlangen post bond streangth within the root canal.Conclusion: Within the limits of this study, it can be concluded that diamond wedge bonding is better than Erlange post bonding.